Study of molecular mechanisms in underwater adhesion systems of sessile animals - Wang, Jining (Nanyang Technological University, 2023)
Through hundreds of millions of years evolution, many marine organisms have developed unique adhesion systems to establish robust adhesion on various types of wetted surfaces which serves as an essential skill for their survival. These underwater creatures are not only frustrating fouling species on man-made architectures but also fascinating biomimetic targets to the design and fabrication of water-resistant adhesives. With the aim to expand the knowledge in underwater adhesion and provide guideline to novel biomimetic designs, we explored the molecular mechanisms in the adhesion systems of two sessile animals, barnacles and mussels.